2020
DOI: 10.1016/j.jcv.2020.104288
|View full text |Cite
|
Sign up to set email alerts
|

A prospective case-control study on the association of Rhinovirus nasopharyngeal viral load and viremia in South African children hospitalized with severe pneumonia

Abstract: A B S T R A C TRhinovirus (RV) role in pathogenesis of severe childhood disease remains controversial. We aimed to explore the association between RV molecular subtyping, nasopharyngeal viral loads and viremia with childhood pneumonia. Nasopharyngeal and blood samples from cases and controls were tested for RV and the 5′ non-coding region sequenced. The cases compared to controls had a similar prevalence of RV detection in the nasopharynx (23 % vs. 22 %, P = 0.66), similar RV species distribution (A, B, C = 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…The serum viral load in HAdV-7 infection is notably high, which is consistent with our previous research on severe cases in children [13]. This observation aligns with studies that have shown an increased serum viral load in children infected with other respiratory viruses [11,37]. Not only did we detect a rise in the copy number of the HAdV-7 ber gene in mouse serum (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The serum viral load in HAdV-7 infection is notably high, which is consistent with our previous research on severe cases in children [13]. This observation aligns with studies that have shown an increased serum viral load in children infected with other respiratory viruses [11,37]. Not only did we detect a rise in the copy number of the HAdV-7 ber gene in mouse serum (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Co-occurrence of bacteria and viruses was common in our study, as measured by either the higher (Ct-value <35) or the lower (Ct-value <30) detection level with rates of 72% and 33%, respectively. A similar rate (76%) of bacterial and viral co-occurrence was reported among the control children from the general population in the PERCH multi-center pneumonia study [ 6 , 29 ]. Variable rates of multiple pathogens have been described in Gambian infants (94%), in healthy Tanzanian children (83%) and in healthy children aged from 6 weeks to 24 months in the Netherlands (38%) [ 32 34 ].…”
Section: Discussionsupporting
confidence: 69%
“…Rhinovirus was found to be equally common in pneumonia cases as in control children in the Pneumonia Etiology Research and Child Health (PERCH) multi-center study performed in seven countries in Africa and Asia [ 6 ]. Also, in children from the Soweto township of Johannesburg in South Africa the prevalence of rhinovirus was similar among pneumonia cases and controls (23% versus 22%) with a much lower prevalence in the control group as compared to the findings of our study [ 29 ]. In Russia, rhinovirus was more frequently detected in healthy controls than in children with community-acquired pneumonia; the same was found in Tanzania for control children as compared to those with acute febrile illness[ 7 , 30 ].…”
Section: Discussionsupporting
confidence: 62%
“…Exacerbations of asthma and other pre-existing diseases such as chronic obstructive pulmonary disease and cystic fibrosis in both adults and children has furthermore been associated with lower respiratory infection with RV (Varkey and Varkey 2008, Stelzer-Braid, Liu et al 2017, Zheng, Wang et al 2018, Cafferkey, Coultas et al 2020, Michi, Love et al 2020, Ortega, Nickle et al 2020, Zhu, Mallia et al 2020. There is also increasing evidence to suggest RV-A and RV-C species may be associated with more severe disease compared to RV-B strains (Lee, Lemanske Jr et al 2012, Megremis, Niespodziana et al 2018, Ng, Oong et al 2018, Baillie, Moore et al 2020, and similar efforts have been made to examine the varied clinical manifestations between RV subtypes (Huang, Wang et al 2009, Moreira, Kamikawa et al 2011, Bruning, Thomas et al 2015, Martin, Kuypers et al 2015, Bergroth, Aakula et al 2020. In order to better understand potential associations between RV species and clinical features among paediatric cases, we aimed to integrate genetic and epidemiological data using Bayesian phylogenetic methods.…”
Section: Introductionmentioning
confidence: 99%